(3GdeLehY (B((3GdeYO dcd bdH eUOhY(B)s
(3ChdgG (B:s
(3hHYO, abO Medfj OGYj GdWQH hGdUHG, ef JdbGA GdeMHhH hGdUHG, hHbGjG QbI aj GdWHGY cGefI, s
(3BNQgG (B:s
(3hbGd(B: (3HYOj Yf MHj CLed dj hCMSf, Yjf dG JfXQ, bdH dG jMRf eG JYde Ef GdCSjI JbWY YQhb GdeMHI s
(3ajg McGjGJ hCTYGQ hehGdjGJ hZjQgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B187 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs